1990
DOI: 10.1002/food.19900340217
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of oxidized lipids with protein Part XVI. Interactions of oxidized ethyl linoleate with collagen

Abstract: The reaction of ethyl linoleate with collagen proceeded at 60 degrees C following the first order kinetics but during the hydroperoxide decomposition the rate constant of the first order decomposition was substantially lower than that of the second order decomposition. Contrary to cellulose, collagen catalyzed the hydroperoxide decomposition. The amount of total oxidation products rose rapidly at the stage of rapid hydroperoxide formation, and slowly afterwards. The browning reaction was fasted in the stage of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…The reaction between cdrbonyl compounds and ethanolamine has also been shown to give browning (Suyama and Adachi 1979;Husain et af 1986). It has been suggested that the ethanolamine group may react with either the hydroperoxides themselves or with aldehydes derived from them to give unstable Schiff bases which react further to give brown pigments by polycondensation reactions with aldehydes (Pokorny et al 1973(Pokorny et al , 1990Tai rt al 1974).…”
Section: Volatiles From the Degradation Of Lipids Heated Alonementioning
confidence: 99%
“…The reaction between cdrbonyl compounds and ethanolamine has also been shown to give browning (Suyama and Adachi 1979;Husain et af 1986). It has been suggested that the ethanolamine group may react with either the hydroperoxides themselves or with aldehydes derived from them to give unstable Schiff bases which react further to give brown pigments by polycondensation reactions with aldehydes (Pokorny et al 1973(Pokorny et al , 1990Tai rt al 1974).…”
Section: Volatiles From the Degradation Of Lipids Heated Alonementioning
confidence: 99%
“…Numerous studies in model systems have shown that oxidizing lipids, peroxides, and certain metal ions cause protein polymerization or fragmentation, insolubilization, amino acid destruction, and formation of protein free radicals and protein-lipid complexes (Roubal and Tappel 1966;Kanner and Karel 1976;Schaich 1980;FUMS et al 1982;Pokorny et al 1990;Meucci et al 1991;Stadtman and Oliver 1991;Uchida et al 1992). These physicochemical modifications could lead to alterations in protein functionality which can be described in terms of protein-protein interaction such as aggregation and gelation, protein-lipid interaction such as emulsification, and protein-water interaction such as viscosity and solubility, resulting in adverse changes in texture and palatability of affected muscle foods. Controlled oxidative processes can be potentially beneficial in processing of some food products.…”
Section: Introductionmentioning
confidence: 99%
“…Site-specific metal-catalyzed oxidation results in loss of enzyme activity and solubility, increases in carbonyl groups and fluorescence, changes in amino acid composition, and increased proteolytic susceptibility (Levine etal., 1990;Meuccietal., 1991). Protein oxidation can also couple with lipid oxidation, resulting in loss of enzyme activity and solubility and formation of protein complexes and nonenzymic browning products (Kanner and Karel, 1976; Funes et al, 1982;Pokorny et al, 1990).…”
Section: Introductionmentioning
confidence: 99%